Identification of a third feline Demodex species through partial sequencing of the 16S rDNA and frequency of Demodex species in 74 cats using a PCR assay. Issue 4 (August 2015) - Ferreira, Diana; Sastre, Natalia; Ravera, Iván; Altet, Laura; Francino, Olga; Bardagí, Mar; Ferrer, Lluís
<x xml:space="preserve">Abstract</x> Background Demodex cati and Demodex gatoi are considered the two Demodex species of cats. However, several reports have identified Demodex mites morphologically different from these two species. The differentiation of Demodex mites is usually based on morphology, but within the same species different morphologies can occur. DNA amplification/sequencing has been used effectively to identify and differentiate Demodex mites in humans, dogs and cats. Hypothesis/Objectives The aim was to develop a PCR technique to identify feline Demodex mites and use this technique to investigate the frequency of Demodex in cats. Methods Demodex cati, D. gatoi and Demodex mites classified morphologically as the third unnamed feline species were obtained. Hair samples were taken from 74 cats. DNA was extracted; a 330 bp fragment of the 16S rDNA was amplified and sequenced. Results The sequences of D. cati and D. gatoi shared >98% identity with those published on GenBank. The sequence of the third unnamed species showed 98% identity with a recently published feline Demodex sequence and only 75.2 and 70.9% identity with D. gatoi and D. cati sequences, respectively. Demodex DNA was detected in 19 of 74 cats tested; 11 DNA sequences corresponded to Demodex canis, five to Demodex folliculorum, three to D. cati and two to Demodex brevis. Conclusions and clinical importance Three Demodex species can be found in cats, because the third unnamed Demodex species is likely to be a distinct species. Apart from D. cati and D. gatoi, DNA from D. canis, D. folliculorum and D. brevis was found on feline skin.